THE EFFECT OF THE NOISE STRESS AND MUSIC ON THE BEHAVIOUR OF FEMALE ALBINO RATS - Hussein, Nizar Jalal; Meshabaz, Ronak A; Sarwar, Aqsa; Oyegoke, Rukayat A.; Khalaf, Fatah M.; Habib, Rekesh S; Kakarash, Nawroz A.; Faraj, Samara Saad; El-Mahdy, Samia Mohsen (Science Journal of University of Zakho, 2026)
Noise is considered an important environmental factor that can affect animal behaviour and productivity. Its impact varies depending on the noise intensity, pattern, duration, and frequency. This research was undertaken to determine the effect of noise stress and playing music on improving the behaviour of female rats. Seventy-five female albino rats were divided into 3 groups, with 25 rats per group. The research groups were Control (no sound exposure), classical music, and noise stress. The sound level for the classic was 80 dB with a frequency of 1 kHz using an MP3 player. The sound level of stress exceeded 150 dB. The results revealed that using classical music led to a significant reduction in the frequency of aggressive behaviours (P<0.01) and an increase in vocalisations (P<0.01). In addition, music and noise stress significantly increased grooming (P<0.05) and climbing behaviour (P<0.05). Furthermore, exposure to the use of music caused increased drinking and feeding behaviours significantly (P<0.01), whereas lying and standing behaviours were decreased (P<0.01). In conclusion, playing music, especially classical music, benefits rats’ welfare by improving their behaviour, as evidenced of decreased vocalization and increased feeding and drinking.